Two new species of Plateros Bourgeois, 1879 (Coleoptera: Lycidae) from Xizang, China - Wang, Cheng-Tao; Fang, Chen; Yang, Yu-Xia; Liu, Hao-Yu (Zootaxa, 2026)
Two new species of Plateros Bourgeois, 1879 are discovered from Xizang, China, and described as P. medogensis sp. nov. and P. yini sp. nov. The description is supported by illustrations of the habitus and male genitalia. The female of P. busynskyi (Bocáková, 1997) is recorded for the first time. A key to the species of Plateros from Xizang is provided.